2013
DOI: 10.1007/s12094-012-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

Beam angle selection for intensity-modulated radiotherapy (IMRT) treatment of unresectable pancreatic cancer: are noncoplanar beam angles necessary?

Abstract: The NCP IMRT was able to significantly decrease bilateral kidney dose, but did not improve other dose-volume criteria. The use of NCP beam angles is preferred only in patients with risk factors for treatment-related kidney dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…This noncoplanar arrangement was based on prior optimization of beam angles and was chosen to mitigate kidney dose, spare skin, and minimize duodenal dose contribution from beam penumbra. 6,7 An example beam arrangement is shown in Fig. 1.…”
Section: C Treatment Planningmentioning
confidence: 99%
“…This noncoplanar arrangement was based on prior optimization of beam angles and was chosen to mitigate kidney dose, spare skin, and minimize duodenal dose contribution from beam penumbra. 6,7 An example beam arrangement is shown in Fig. 1.…”
Section: C Treatment Planningmentioning
confidence: 99%
“…For the stomach, duodenum and bowel, we applied an Į/ȕ value of 3.5 Gy; for the spinal cord, 2.0 Gy; for liver, 3.0 Gy; for the skin, 10.0 Gy [5] . BED=nd(1+d/(Į/ȕ) ) (1) After dividing the target, we need to count the total biological dose of the sensitive organs in PTV1 and PTV3 [6] : BED total = BED 1 + BED 3 (2) BED total refers to the total biological dose while BED 1 and BED 2 refer to the biological dose of sensitive organs in PTV1 and PTV3, respectively.…”
Section: The Calculation Of Biological Equivalent Dosementioning
confidence: 99%
“…These results show that the tumor coverage of divisional target plan is obviously better than a single target plan. 4.2 It's the dose of OARs which decides if the treatment plan could be implemented, thus the dose superposition of sensitive organs is one of the most important aspects we need to consider about when designing divisional target plans [6]. The dose threshold given in report TG101 is the dose standard of five times' fractioned irradiation.…”
Section: Liver Is a Soft Tissue Which Is Influenced By Respirationmentioning
confidence: 99%
“…They concluded that technique selection should be individualized, based on patient-specific clinical and dosimetric parameters. Chang et al [5] examined the utility of noncoplanar beam angles in IMRT for the management of 16 pancreatic cancer patients. The use of NCP beam angles was preferred only in patients with risk factors for treatment-related kidney dysfunction.…”
Section: Introductionmentioning
confidence: 99%